ENVIRONMENTAL LEADERSHIP ON GREEN COMPETITIVE ADVANTAGE WITH GREEN HUMAN CAPITAL AS MODERATION - Rachmawati, Sistya; Murwaningsari, Etty (Jurnal Riset Bisnis dan Manajemen, 2024)
The purpose of this study is to analyze (1) The influence of environmental organizational culture, environmental leadership, and environmental capability on green competitive advantage. (2) Green human capital moderates the influence of environmental organizational culture, environmental leadership, and environmental capability on green competitive advantage. Conducted with taking the secondary data namely all company listed on the Indonesian Stock Exchange whith purposive sampling criteria during 2018-2022 period with 256 observation. The results of this study indicate environmental organizational culture and environmental capability have no influence on green competitive advantage, while environmental leadership has influence on green advantage, green human capital strengthens the influence of environmental organizational culture. Variable control green structural capital and green relational capital has no significant influence on green competitive advantage.